A retrospective database analysis to evaluate the potential of ex vivo lung perfusion to recruit declined lung donors. (13th July 2017) - Martens, An; Van Raemdonck, Dirk E; Smits, Jacqueline; Verleden, Stijn E; Vos, Robin; Vanaudenaerde, Bart M; Verleden, Geert M; Degezelle, Karlien; Desschans, Bruno; Neyrinck, Arne P
Summary: Ex vivo lung perfusion (EVLP) is currently used for both standard and extended‐criteria donor (ECD) lungs. To enlarge the donor pool, we might have to extend the threshold for ECD donation. The purpose of this study was to estimate how many additional ECD lungs could be recruited by EVLP. We reviewed all multi‐organ donors (MODs) from our collaborative donor hospitals (January 2010–June 2015). All unused lung donors were categorized using registered donor data and evaluated by two independent investigators to identify which lungs could be transplanted after EVLP. 584 MODs were registered at our transplant center. 268 (45.9%) were declined as lung donor at the moment of registration, and 316 (54.1%) were considered as a donor for lung transplantation. In the latter, lungs from 220 (37.7%) donors were transplanted and 96 donors (16.4%) were not. We identified 78 of 364 declined donors (21.4%) whose lungs could potentially become transplantable after EVLP. With this retrospective database analysis of unused lung donors, we identified a large potential for EVLP to further increase the donor pool in transplant centers where the majority of donor lungs are already extended.